Capacidade dinâmica e ambidestria: um estudo de caso no setor têxtil - Holanda, Fernanda Marques de Almeida (2020)
Increasingly dynamic and complex environments encourage organizations to develop strategic resources and internal competencies, thus incorporating a set of combinations of capabilities to remain competitive. In this way, the dynamic capability allows the configuration of different forms of performance, either through a new business or expansion of an existing business, or through the creation of a product or production process. The dynamic capability has a connection with the area of studies in ambidexterity, as it involves activities based on processes and new markets, in a routine and deliberate manner. When considering that the development of new capacities represents a process, this study aims to understand the contribution of ambidexterity in the microfoundations of dynamic capacity in an organization in the textile sector. The relevance of the work is supported by the contribution of verifying the organizational reality in complex environments, making it possible to identify structures that collaborate with a better performance of organizations, in addition to the discussion of new configurations of resources that provide a source of differentiated advantage. The methodological procedures involved a qualitative approach, with a described-exploratory study, with a single case study method carried out in an industry in the textile sector. For that, in-depth interviews were used with content analysis as a technique. The results pointed to a collaborative business model, with great participation of leaders, technological changes and reconfiguration of assets. Elements related to ambidexterity and dynamic capability were identified in an integrated manner. The aspects related to structures, context and resources were elements that contributed to the construction of a culture directed towards ambidexterity through the micro foundations of dynamic capability.